Job Satisfaction as A Mediator between Nonfinancial Compensation on Employee Performance of Bank Indonesia in South Sulawesi - Haikal Haikal; Sumardi Sumardi; Abdullah Sanusi (Universitas Mercu Buana, 2023)
The objectives of this study were, to analyze the effect of non-financial compensation and job satisfaction on employee performance; and to analyze the mediating role of job satisfaction. The minimum sample for this research is 80 employees of Bank Indonesia Representative Office of South Sulawesi Makassar City.The test tool used is SEM-SmartPLS 4 vers. 4.0.9.3 as a statistical test tool. The results of this study indicate that non-financial compensation is no less important than financial compensation, and one of the sources of job satisfaction is non-financial compensation. This study proves that non-financial compensation has a positive and significant effect on job satisfaction and employee performance. In addition, job satisfaction also has a significant effect on employee performance, and mediates the relationship between non-financial compensation and employee performance at the Makassar City Representative Office of Bank Indonesia South Sulawesi.